2014
DOI: 10.1111/jfpe.12089
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherms of Maria Biscuits from Different Brands

Abstract: This study aimed to determine the adsorption curves of Maria biscuits from different brands at temperatures of 25 and 40C. The equilibrium between the sample and the atmosphere was achieved by placing the samples inside flasks containing saturated salts, at the temperatures studied for 5 days, to allow reaching equilibrium.From the results, it was possible to observe that by increasing the temperature, the stability of the product is augmented, as for the same moisture content the water activity is greatly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…1a, b) exhibited a tendency to change shape during storage time, showing, according to BET classification, the characteristics type III shape (or 'J' shaped) during the first five days of storage; after this period the shape they assumed was more similar to a sigmoid-curve of type II. Above 0.75 a w the curves showed a steep rise attributable to the dissolution of sugars in the product aqueous phase (Bourlieu et al, 2008;Guiné et al, 2014). The equilibrium moisture contents near saturation, for a w ranging from 0.85 to 0.95, significantly increased: 19.8% at the beginning (0 day), 29.7% at 15 days, 35.1% at 40 days and 40% at 95 days.…”
Section: Sorption Isothermsmentioning
confidence: 92%
See 2 more Smart Citations
“…1a, b) exhibited a tendency to change shape during storage time, showing, according to BET classification, the characteristics type III shape (or 'J' shaped) during the first five days of storage; after this period the shape they assumed was more similar to a sigmoid-curve of type II. Above 0.75 a w the curves showed a steep rise attributable to the dissolution of sugars in the product aqueous phase (Bourlieu et al, 2008;Guiné et al, 2014). The equilibrium moisture contents near saturation, for a w ranging from 0.85 to 0.95, significantly increased: 19.8% at the beginning (0 day), 29.7% at 15 days, 35.1% at 40 days and 40% at 95 days.…”
Section: Sorption Isothermsmentioning
confidence: 92%
“…1b), indicating a different ability of the product to bind water in this isotherm zone, probably because of water sorption by the starch-based components of the biscuit matrix (McMinn et al, 2007). These macromolecules are rich in polar sites that behave as active sorption centres (Guiné et al, 2014). It is well known that the behaviour and shape of the moisture sorption isotherms depend on the state of the system constituents ( Barbosa-Cánovas et al, 2007).…”
Section: Sorption Isothermsmentioning
confidence: 97%
See 1 more Smart Citation
“…The cookies' moisture sorption isotherm is shown in Figure 1. The isotherm showed a type III shape, as classified by Brunauer et al 49 While type II isotherms are also reported for biscuits and cookies, this is a common finding for sugary confectionery products 13,50–53 . As discussed by Lewicki, 54 these curves possess inflexion points that indicate crucial moisture levels.…”
Section: Resultsmentioning
confidence: 78%
“…The accuracy of GAB modeling can be seen in Figure 2. GAB is expressed in accordance with several types of food such as biscuits, chicken wheat crips, and extrudate products (Bhardwaj et al, 2017;Guiné et al, 2014;Wani & Kumar, 2016). GAB model is known as a superior model because its success in modeling many food products in a wide "a w " range of 0.1-0.9 (Kurniawan, 2018;Bhardwaj et al, 2017).…”
Section: Curves Mathematical Modeling and Slope Of Moisture Sorptiomentioning
confidence: 99%